The Intellect Islamic Thought: Mind and Heart - Crow, Karim Douglas (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2018)
The Arabic term al-‘aql/“intelligent/understanding/reason” is one among half-a-dozen of the most important concepts occurring throughout Islamic experience and thought. From the beginning of the Islamic Era, it had been an opaque term, and Muslim scholars did not always agree that ‘aql was univocal in meaning. In its early Islamic unfolding the concept of ‘aql comprised the intersection of primarily Arab and Qur’anic as well as Biblicic components with Hellenic and Iranian traditions.